A new breakable stent for recoarctation in early infancy: Preliminary Clinical Experience. Issue 4 (2nd January 2016) - Grohmann, Jochen; Sigler, Matthias; Siepe, Matthias; Stiller, Brigitte
Abstract : Objectives: Transcatheter treatment of aortic coarctation (CoA) via stent implantation has become an established treatment option depending on the patient's age and CoA type. Background: The Osypka BabyStent ® is a low‐profiled, balloon‐expandable cobalt‐chrome stent to treat aortic CoA in infants, which is breakable to permit unrestricted growth. We hereby evaluated our initial clinical experience to demonstrate the feasibility and efficacy of this new nonlicensed device, which we have occasionally implanted in critically ill patients or when redo‐surgery would entail an excessively high risk. Methods: Retrospective single‐center analysis of all available data during and after treatment with a BabyStent implanted in infants with considerable re‐CoA or reobstruction of the aortic arch after former surgery. All interventions took place under fluoroscopy and conscious sedation with local anesthesia or general anesthesia. Results: Five BabyStents were implanted in four infants with technical success in all of them—median age 10 weeks (range 5–21), median bodyweight 3.8 kg (range 2.7–4.5). Aortic diameters enlarged from median 2.25 mm (range 1.5–3.3) to median 5.3 mm (range 4.6–6.0). The follow‐up period lasting up to 26 months (median 8.5, range 2–26) was uneventful concerning stent‐related complications. Conclusions: BabyStent ® implantation for recoarctation was effective. However, our initial experience with the device is limited to short‐ and midterm follow‐up only. None of the stents was subsequently overdilated with the intention to break due to our patients' limited somatic growth so far. A multicenter survey has been initiated to justify device approval. © 2016 Wiley Periodicals, Inc.